Pengaruh Model Pembelajaran Think Pair Share terhadap Peningkatan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Agama Kristen - Simanullang, Ferry Josua; Munthe, Bangun; Silalahi, Jojor (Attractive : Innovative Education Journal, 2024)
The purpose of this research is to see the influence of the Think Pair Share learning model on improving student learning outcomes in Christian religious education subjects in Class IX of Talitakum Private Middle School, Medan. This type of research is an experiment with the research population, namely all class IX students at Talitakum Medan Private Middle School, where 1 class was selected as a sample and then divided into 2 classes, namely class IX-A as the experimental class taught using the Think Pair Share model and class IX-B as control class taught using the conventional model. The instrument used is a test in the form of true or false. After carrying out different treatments, the average post-test score for the experimental class was 82.33 with a standard deviation of 5.77 and the average post-test score for the control class was 71 with a standard deviation of 5.93. From the results of hypothesis testing with ? = 0.05, it is obtained? T?_(count ) ? T_table (4.84 > 2.074) so ??that H_0 is rejected and conversely H_a is accepted. So it can be concluded that there is an influence of the Think Pair Share Learning Model on Increasing Student Learning Outcomes in Class IX Christian Religious Education Subjects at Talitakum Private Middle School, Medan. During the learning process in the experimental class, students' learning activities were observed and the final score was in the very good category. Keywords: Think Pair Share Model, Increasing Leaerning Outcome, Learning Outcome